Soret and nonuniform heat source/sink effects in micropolar nanofluid flow over an inclined stretching sheet - Machindranath Diwate; Pradeep G. Janthe; Nitiraj V. Kulkarni; S. Sunitha; Jagadish V. Tawade; Nodira Nazarova; Manish Gupta; Nadia Batool (International Journal of Thermofluids)
This study investigates the heat and mass transfer dynamics of micropolar nanofluid flow over a stretching sheet subjected to nonuniform heat sources/sinks. The influence of key factors, such as Brownian motion, thermophoresis, chemical reactions, and thermal radiation, on the velocity, temperature, and concentration profiles of the nanofluid is explored. The research employs advanced numerical methods, using the bvp4c solver, to solve the governing equations and compute the effects of various physical parameters on fluid dynamics. The results demonstrate that an increase in the magnetic field strength reduces the fluid velocity, while changes in material properties can lead to higher fluid speeds. Furthermore, the Soret effect significantly enhances mass transfer and the heat transfer at the surface diminishes as A* and B* increases, with implications for applications in separation technologies and desalination. A detailed analysis of the influence of the Soret number, Brownian motion, and thermophoresis reveals critical insights into thermal transport and solute distribution in the boundary layer. These findings have practical applications in cooling systems, biomedical engineering, and other industries where precise control of heat and mass transfer is crucial.